Abstract 091: Intraventricular milrinone for management of vasospasm following aneurysmal subarachnoid hemorrhage - Seyed Mostafa Razavi; Mahika Khurana; Cynthia Zevallos Mau; Divyajot Sandhu (Stroke: Vascular and Interventional Neurology)
Introduction Aneurysmal subarachnoid hemorrhage (aSAH) accounts for about 10% of hemorrhagic strokes [1] and holds a high mortality and morbidity rate. [2, 3] Vasospasm is one of the more devastating complications of aSAH. Novel imaging modalities have drastically improved our ability in prompt detection of vasospasm in these patients. However, clinical management of this complication is still debated among experts. [4] Systemic cerebral vasodilators are widely used in aSAH patients, but guidelines for interventional and rescue procedures are not well developed. [5] Methods Here, we report a case of severe vasospasm following aSAH that was successfully treated with intraventricular injection of milrinone through external ventricular drain (EVD) in conjunction to standard therapy. Results A 70‐year‐old man with a history of diabetes, hypertension, and hyperlipidemia was brought to the emergency department after he was found down and unresponsive. He was intubated by EMS on route. Head CT on arrival showed a diffuse subarachnoid hemorrhage, more prominent in the posterior fossa, and grade IV on the modified Fisher scale. An initial DSA showed a ruptured aneurysm in the second segment of the right posterior inferior cerebellar artery, second segment. A right frontal EVD was placed on the second day. Hemodynamic augmentation was achieved with intravenous and intraventricular milrinone. Cerebral arterial patency was evaluated with daily transcranial doppler (TCD). The patient did not show any evidence of vasospasm until day 9 where TCD revealed severe vasospasm in the basilar and bilateral vertebral arteries, as well as mild vasospasm of anterior and middle cerebral arteries. Intraventricular milrinone was injected into the EVD in from day 9 to day 12. Using sterile technique, 4 mL of CSF was removed followed by the injection of 0.87mg (2mL) of milrinone into the EVD via a three way stop cock. EVD was then flushed with 2mL of preservative‐free saline and clamped for 1 hour. This procedure effectively improved vasospasm on serial TCDs and also DSAs (Figure1). The patient underwent several DSA’s on days 10, 14, 19, 20, and 21 with targeted intraarterial milrinone and verapamil injections. His final TCD showed only mild middle cerebral artery and moderate basilar artery vasospasm. At that point, no more intervention was deemed necessary. A ventriculoperitoneal shunt was also placed. CT scan before discharge showed mild improvement in ventricular size and stable SAH blood products. The course of hospitalization was complicated by hyponatremia, atrial fibrillation, and respiratory failure with inability to wean off ventilator, resulting in tracheostomy and gastrostomy tube placement. The patient was discharged in stable condition on day 30 to a rehabilitation center. Conclusion Intraventricular milrinone in addition to standard therapy can be an effective method in treatment of severe vasospasm in aSAH patients.